2021
DOI: 10.3390/genes12030439
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Ethephon-Induced IDA-Like Genes from Mango, and Elucidation of Their Involvement in Regulating Organ Abscission

Abstract: In mango (Mangifera indica L.), fruitlet abscission limits productivity. The INFLORESCENCE DEFICIENT IN ABSCISSION (IDA) peptide acts as a key component controlling abscission events in Arabidopsis. IDA-like peptides may assume similar roles in fruit trees. In this study, we isolated two mango IDA-like encoding-genes, MiIDA1 and MiIDA2. We used mango fruitlet-bearing explants and fruitlet-bearing trees, in which fruitlets abscission was induced using ethephon. We monitored the expression profiles of the two Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…At the same time, ethylene can also induce the formation of the abscission layer and can cause the abscission of flowers and fruits. In mango, after ethylene induction, the expression of MiIDA1 and MiIDA2 had upregulated and the formation of the abscission layer was promoted (Rai et al, 2021). In Camellia oleifera, CoIDAs are abscission-associated genes, which can be induced by ethylene and push forward the formation of the abscission layer (Yang et al, 2021).…”
Section: Formation Of the Abscission Layer Of The Cotton Boll Stalk I...mentioning
confidence: 99%
“…At the same time, ethylene can also induce the formation of the abscission layer and can cause the abscission of flowers and fruits. In mango, after ethylene induction, the expression of MiIDA1 and MiIDA2 had upregulated and the formation of the abscission layer was promoted (Rai et al, 2021). In Camellia oleifera, CoIDAs are abscission-associated genes, which can be induced by ethylene and push forward the formation of the abscission layer (Yang et al, 2021).…”
Section: Formation Of the Abscission Layer Of The Cotton Boll Stalk I...mentioning
confidence: 99%
“…In an earlier study, the application of exogenous ETH caused all litchi fruitlets to drop within 4 days of the treatment [ 48 ]. The formation of the abscission layer is promoted by ethylene in both mango [ 49 ] and cotton [ 50 ]. In accordance with these findings, in another study, the abscission layer started to form at 12 h after a treatment with 400 mg/L ethylene treatment of cotton bolls [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported that the IDA transcript increased in the abscission zone (AZ) of the wilted plants at 40% SWC, and then it was further increased 1 day after rewatering (Patharkar & Walker, 2016). Ethylene was reported to induce ida expression in various plant species (Meir et al, 2019; Rai et al, 2021). The possibility that the increase of the IDA transcript in this system is ethylene‐dependent has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct IDA family members of tomato and soybean (Tucker & Yang, 2012), citrus (Estornell et al, 2015), lychee (Ying et al, 2016), oil palm (Tranbarger et al, 2019), yellow lupine (Wilmowicz et al, 2018), and most recently from mango (Rai et al, 2021) were characterized and demonstrated to be involved in organ abscission. It should be noted that the expression of these ida gene family members increased in the above species by ethylene or ethephon application.…”
mentioning
confidence: 99%